MENGELOLA KEUANGAN BAGI WIRAUSAHA PEMULA - Yulia, Yulia (The Pontianak State Institute of Islamic Studies, 2014)
An effective financial strategy includes the management and supervision of financial records, planning, and management of budget in order to achieve the goal of maximizing benefit for capital owners. The effectiveness of financial management will greatly be determined by the objectives of businesses owned by the entrepreneurial novices in their strategic plan document. If a business goal is to build a vast business scale, increase market share and the number of consumers, the financial strategy by setting a high profit margin, only using its own capital, and reproducing fixed assets may not be suitable. To support the business objectives, it will be more appropriately to set a profit margin that is not too large so that prices are pretty competitive. Debt is used because of limited capital, and fixed asset through rent is employed rather that self-owned in order to minimize working capital needed. The effective financial management can make use of the balance sheet, income statements and cash flow statements. The balance sheet or also known as a statement of net worth, is the form of the report that explains the value of all assets and the value of all the obligations that we have and the amount of capital itself (liability). From the balance sheet, we can see the value added to the capital.Meanwhile, the income statement is a report that shows performance of profit accumulation in a certain period of time. The value of the profit is obtained from the reduction of the amount of revenue generated by required fees